TATÄ•NGÄ•R : DIAGNOSA DALAM USADHA BALI - Suweka Oka Sugiharta, I Putu (Institut Hindu Dharma Negeri Denpasar, 2020)
Tat?ng?r occupies a very important role in Balinese usadha. Although not exactly the same, Tat?ng?r has similarities with diagnosis in medical treatment. In Bali there are various ways to diagnose both those that originate from oral tradition and text tradition. Sometimes between one healer and another healer has a different way to detect the patient's disease. A healer learns the diagnosis from reading traditional medical books (lontar usadha), learning from a teacher, or discovering it based on his experience.Sometimes a balian is able to detect disease through ways that are not understood by general logic, even his own reason. This phenomenon is known in Bali as a horn. Of course, how to detect this kind of disease is very difficult to teach others. Given the variety of ways of diagnosing diseases in the Balinese usadha, studies in this field can be done to the widest possible range of perspectives.